2012
DOI: 10.1097/tp.0b013e3182529b76
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Human Amniotic Mesenchymal Stem Cells and Their Chondrogenic Differentiation

Abstract: These results suggest that HAMα cells correspond to MSCs that are highly proliferative and multipotent. Their chondrogenic potential and low immunogenicity indicate that HAMα cells could be an allotransplantable cell resource for cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…The results demonstrated that various factors were able to induce the ADSCs to differentiate into different directions, and that the ADSCs derived from mesoderm were able to differentiate into endodermal and ectodermal cells. The autologous features of these stem cells, in combination with their distinct pluripotency and easy acquirement, make ADSCs an attractive choice for future tissue engineering and cell-based therapies (2830). …”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that various factors were able to induce the ADSCs to differentiate into different directions, and that the ADSCs derived from mesoderm were able to differentiate into endodermal and ectodermal cells. The autologous features of these stem cells, in combination with their distinct pluripotency and easy acquirement, make ADSCs an attractive choice for future tissue engineering and cell-based therapies (2830). …”
Section: Discussionmentioning
confidence: 99%
“…Human amniotic epithelial cells are derived from the epiblast, and human amniotic mesenchymal stromal cells are derived from the hypoblast. [26][27][28] Mesenchymal stem cells may modulate the immune response. The T lymphocyte is a major effector of the adaptive immune response, and mesenchymal stem cells may modulate the function of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were stained by incubating with antibodies of mesenchymal stem cell markers (anti-human CD90-FITC, and anti-human CD105-Alexa647; BD Biosciences) 14,15 for 30 min. Primary antibodies were diluted according to the manufacturer's instructions.…”
Section: Facs Analysesmentioning
confidence: 99%